IRE Teachers' Efforts to Improve Digital Literacy to Strengthen Religious Interaction towards a Good Digital Citizenship Society - Pandu Hyangsewu; Hilman Taufiq Abdullah; Achmad Faqihuddin; Abdullah Muflih; Indah Sari (Universitas Muhammadiyah Mataram, 2024)
Digital literacy, including Islamic Religious Education (IRE), has become essential in modern education. This article discusses the efforts of IRE teachers in improving digital literacy to strengthen students' religious interactions toward forming a Good Digital Citizenship society. This study uses a qualitative approach to explore the experiences and strategies of IRE teachers in Junior High Schools (JHS) and Senior High Schools (SHS) in integrating technology into learning. Data were obtained through in-depth interviews with 10 IRE teachers skilled in digital literacy and accustomed to using digital media and content in teaching. The data were analyzed using the Miles and Huberman framework, involving data reduction, data display, and conclusion drawing to identify patterns and themes related to digital literacy integration. The study results show that IRE teachers integrate technology through digital tools such as Google For Education, Quizizz, Canva, and video platforms such as YouTube to enrich the learning experience. Teachers also create digital content such as interactive modules, educational videos, and podcasts, which engage students and expand access to relevant religious information. Additionally, teachers provide digital literacy education that includes training on digital ethics, online security, and responsible social media usage. This study concludes that digital literacy in IRE supports students' technological skills and helps shape their moral character in the digital world. This effort significantly contributes to forming students as good digital citizens who can interact ethically and productively in the digital space. The implications of this study indicate the importance of ongoing digital literacy training for teachers and students to support relevant religious education in the digital era.